1997
DOI: 10.1007/bf02742935
|View full text |Cite
|
Sign up to set email alerts
|

MRI diagnosis of intramedullary metastases from extra-CNS tumors

Abstract: The purpose of this study was to evaluate the topography, morphology and contrast enhancement of the intramedullary metastases (IM) from extra-CNS neoplasms. We report the results of a multicenter retrospective study on 18 patients with 26 IM examined with a 0.5T MR imaging system; intravenous injection of Gd-DTPA was performed in all cases. We found that the lesions are most frequently single, oval shaped, and small, with little or no deformation of the spinal cord (14 of 26 IM). They appear isointense on spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Thus, the assumption of metastasis remains questionable. Meningeal locations were far from the intramedullary metastases in three cases described by Crasto et al [5], supporting the pathogenesis of intramedullary metastases as being due to vascular dissemination. In nine of ten cases of extramedullar metastases reported by Perrin et al [11], secondary brain tumours were demonstrated, favouring the concept that spinal metastases represent tertiary deposits following dissemination via the CSF [12].…”
Section: Disseminationmentioning
confidence: 62%
See 1 more Smart Citation
“…Thus, the assumption of metastasis remains questionable. Meningeal locations were far from the intramedullary metastases in three cases described by Crasto et al [5], supporting the pathogenesis of intramedullary metastases as being due to vascular dissemination. In nine of ten cases of extramedullar metastases reported by Perrin et al [11], secondary brain tumours were demonstrated, favouring the concept that spinal metastases represent tertiary deposits following dissemination via the CSF [12].…”
Section: Disseminationmentioning
confidence: 62%
“…The amount of oedema can best be observed on T2-weighted images as an area of hyperintensity that is extensive in metastases [7]. Intense contrast enhancement of the solid parts of metastases is mostly present either as ring-shaped enhancement or as a homogeneous nodular mass [5]. With the exception of haemangioblastomas, epidermoid tumours, and lipomas, MRI is unable to predict the histological composition with certainty.…”
Section: Computed Tomography and Magnetic Resonance Imagingmentioning
confidence: 99%
“…8 One recent small series of 8 ISCM patients reviewed the published literature of an additional 293 cases but did not specifically assess MR imaging findings. 9 The large amount of spinal cord edema compared with the length of the enhancing ISCM has been known anecdotally and described in a smaller series with low field strength MR imaging examinations, 10 as well as in other small series; for instance, in 3 patients in a study by Sze et al 11 However, to our knowledge, this has not been systematically reported and quantified in a large series by use of modern MR imaging scanners.…”
Section: Cord Lesion (Arrow) Is Associated With a Large Amount Of Cormentioning
confidence: 91%
“…Physicians diagnose only 5% of these metastases before death 18 however, with advanced imaging techniques like MRI, there has been recorded a progressive increase in its frequency 3,8,9,19 . ISCM is found together with leptomeningeal disease (LMD) in 15-55% of the cases 3,9,20 .…”
Section: Epidemiologymentioning
confidence: 99%
“…Gadolinium MRI has a high sensitivity in identifying such lesions. Furthermore, T2-weighted imaging demonstrates the edema related to metastasis with great success 3,10,11,16,19,20,29 . MRI with gadolinium has proven high sensitivity in the detection of intramedullary and spinal leptomeningeal neoplasms 29,30 .…”
Section: Diagnosismentioning
confidence: 99%